Unexpected "ferrate" species as single-component catalyst for the cycloaddition of CO2 to epoxides. Issue 51 (September 2021) - Panza, Nicola; di Biase, Armando; Gallo, Emma; Caselli, Alessandro
Highlights: A novel "ferrate" with high activity in the CO2 cycloaddition to epoxides. No need for a co-catalyst (Lewis base). High conversions and selectivities under solvent-free and mild reaction conditions. TOF up to 135 h −1 and TONs, up to 1020. The bifunctional nature of the catalyst is assured by the peculiar properties of the ferrate anion. Abstract: A soluble ferrate salt was synthetized by treating a novel protonated pyridine-containing macrocyclic ligand with iron(III) bromide. Its good activity as a stand-alone catalyst in CO2 cycloaddition reactions to epoxides was assessed. Good yields of cyclic organic carbonates were obtained, especially with terminal epoxides, under solvent-free reaction conditions (T = 100 °C, P (CO2 ) = 0.8 MPa), without the need of any Lewis base as the co-catalyst. This system proved to be active and selective towards the cyclic carbonates formation, with a broad reaction scope. A scale-up reaction on 2.5 mL of propylene oxide was performed and the robustness of the catalyst was proved up to three recycles (TON = 1020).